The evolutionary connection among classes of close binaries - Bondarenko, I. I.; Perevozkina, E. L. (Одеські астрономічні публікації, 2017)
The evolutionary connection of different types of close binaries is suggested. The early type contact systems are presented as one of the evolutionary stages of close binaries.